Edge‐Fluorinated Graphene Nanoplatelets as High Performance Electrodes for Dye‐Sensitized Solar Cells and Lithium Ion Batteries. (8th January 2015) - Jeon, In‐Yup; Ju, Myung Jong; Xu, Jiantie; Choi, Hyun‐Jung; Seo, Jeong‐Min; Kim, Min‐Jung; Choi, In Taek; Kim, Hong Mo; Kim, Jae Cheon; Lee, Jae‐Joon; Liu, Hua Kun; Kim, Hwan Kyu; et al.
Abstract : Edge‐selectively fluorinated graphene nanoplatelets (FGnPs) are prepared by mechanochemically driven reaction between fluorine gas (20 vol% in argon) and activated carbon species from graphitic C–C bonds unzipped by high‐speed stainless steel balls with a high kinetic energy. The fluorination at edges of the unzipped graphene nanoplatelets (GnPs) is confirmed by various analytical techniques while the content of fluorine in FGnPs is determined to be 3.0 and 3.4 at% by X‐ray photoelectron spectroscopy and energy‐dispersive X‐ray spectroscopy, respectively. Because of the large difference in electronegativity between carbon ( χ = 2.55) and fluorine ( χ = 3.98) and the strong C–F bond, the edge‐fluorination of GnPs can provide the maximized charge polarization with an enhanced chemical stability. Thus, electrodes based on the resultant FGnPs demonstrate superb electrochemical performance with excellent stability/cycle life in dye‐sensitized solar cells (FF: 71.5%; J sc : 14.44 mA cm −2 ; V oc : 970 mV; PCE: 10.01%) and lithium ion batteries (650.3 mA h g −1 at 0.5 C, charge retention of 76.6% after 500 cycles). Abstract : Edge‐selectively fluorinated graphene nanoplatelets (FGnPs) are prepared by simple mechanochemical ball‐milling graphite in the presence of fluorine/argon (20/80, v/v). The FGnPs demonstrate superb electrochemical performance with excellent stability/cycle life in dye‐sensitized solar cells and lithium ion batteries.